KARDIOCHIRURGIA DOROSŁYCHPost-infarction pseudoaneurysm and mitral regurgitation successfully repaired by primary closure of the pseudoaneurysm neck. Case report - Zieliński, Dariusz; Dyk, Wojciech; Jasińska, Małgorzata; Konka, Marek; Zygier, Marcin (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
The authors report a case of post-infarction pseudoaneurysm and mitral regurgitation successfully repaired by primary closure of the pseudoaneurysm neck.